2010
DOI: 10.1042/cbi20090160
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural analysis of interneuronal syncytial perforations

Abstract: The structural regularities of the organization of interneuronal syncytial cytoplasmic connections between neuronal bodies in gyrus dentatus and CA1 and CA2 (CA is cornu ammonis) of hippocampus, as well as between cell neurites of the caudal mesenteric ganglion were studied by transmission electron microscopy. The syncytial perforations are located only on the base of tight junctions. The perforations have rounded edges corresponding to the fusion edges of perforated membranes of adjacent neurons - or where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
(7 reference statements)
1
5
0
Order By: Relevance
“…We observed a similar phenotype in animals deficient in UNC-70/β-spectrin, a genetic background in which the axons of C. elegans motor neurons undergo spontaneous cycles of breaks followed by regeneration 30 . We observed that unc-70 mutant animals display aberrant PLM axonal morphology …”
Section: Introduction and Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…We observed a similar phenotype in animals deficient in UNC-70/β-spectrin, a genetic background in which the axons of C. elegans motor neurons undergo spontaneous cycles of breaks followed by regeneration 30 . We observed that unc-70 mutant animals display aberrant PLM axonal morphology …”
Section: Introduction and Resultssupporting
confidence: 54%
“…EFF-1 localization has been characterized in multiple tissue and cell types, albeit with somewhat varied results. In some cells, EFF-1 has been observed accumulating at cell-cell borders prior to fusion 29,30,34,82 . However, another study using immunostaining demonstrated that endogenous EFF-1 instead localized predominantly to intracellular compartments, and was present only transiently at the membrane.…”
Section: Post-translational Regulation Of Eff-1mentioning
confidence: 99%
See 3 more Smart Citations